Emergency care visits at a South African hospital: Implications for healthcare services and policy - Jacob A. Adewole; John M. Tumbo; Henry I. Okonta (South African Family Practice)
Background: A robust knowledge on the pattern of use of emergency care resources not only serves as an indicator of universal access to care but also provides a basis for quality improvement within the health system. This study was undertaken to describe the pattern of emergency room visits at Brits District Hospital (BDH) in North West province, South Africa. The objectives of this study were to determine the sociodemographic characteristics of emergency department (ED) users and other patterns of ED use.